Acceptance of Mini-CEX Use with Technology Acceptance Model (TAM) Theoritical Approach - Hikmat Pramajati; Nunung Siti Sukaesih; Emi Lindayani; Halimatusyadiah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aim: Obtain an overview of the level of acceptance of nursing clinic educators using mini-CEX as an assessment method. Method: This research is a descriptive study with 62 subjects were clinical instructors, conducted training first, then the technique of data collection using 2 instruments namely mini-CEX format and modified TAM. Result: 98.4% of respondents can use mini-CEX with graduation criteria above 75% and the graduation of 18.6. Product moment correlation test results for all items TAM significance value> 0.25, then all items are declared valid with a significance of 95%. TAM questionnaire reliability with Alpha Croanbach's test is 0.957. The results of data analysis using the t-test with a limit on the acceptance value of using mini-CEX using the TAM questionnaire was 70% found that the test results showed sig 0,000 (<.0.05). Conclusion: Mini-CEX can be used as a clinical performance appraisal instrument for nursing students, with a high level of acceptance measured by TAM.